Age- and sex-dependent differences in patients with severe asthma included in the German Asthma Net cohort - Milger-Kneidinger, Katrin; Korn, Stephanie; Buhl, Roland; Hamelmann, Eckard; Herth, Felix; Gappa, Monika; Drick, Nora; Fuge, Jan; Suhling, Hendrik (Respiratory medicine, 2020)
Background - Severe asthma affects less than 5% of asthmatics, but is associated with high costs and increased mortality. The aim of this study was to assess age- and sex-dependent differences in this patient group. - Methods - Retrospective analysis of 1317 children and adults with severe asthma who are included in the German Asthma Net registry. - Results - There were more adults than children in the registry and patients’ mean age was 52. Apart from children <18 years, there were more women (57%) than men. The age of first diagnosis ranged from 0 to 76 years. 38% of patients had a positive bronchial reversibility after short acting bronchodilators. Quality of life, FEV1 and MEF 25 decreased with older age whereas treatment with oral steroids and monoclonal antibodies increased. An anti-eosinophil treatment was most frequently used in patients aged around 57 years, while an anti-IgE treatment was used in all age-groups including children. There were sex-dependent differences with lower values in men for FEV1, FVC, MEF 25 and DLCO. Yet, women were more frequently unable to work than men due to the disease. - Conclusion - In patients with severe asthma, clinical characteristics, but also treatments differed between age groups and between the sexes, reflecting different phenotypes of the disease.
Gesehen am 30.03.2020